Specific admission nursing consultation for SARS-CoV-2 in prison units: prevalence and associated factors - Gláucia Oliveira Abreu Batista Meireles; Ketllen Raiara Ferreira Santos Freires; Cácia Régia de Paula; Águeda Maria Ruiz Zimmer Cavalcante; Leticia Cortaza Ramírez; Márcia Alves Dias de Matos; Nara Rubia de Freitas; Marcos André de Matos (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT: Objective: To estimate the prevalence and factors associated with the performance of specific admission nursing consultations for SARS-CoV-2 in individuals deprived of liberty with COVID-19 in prison units in Central Brazil. Method: Analytical cross-sectional study conducted between May and September 2020 through individual interviews and lateral flow immunochromatography tests to detect IgM/IgG antibodies for SARS-CoV-2. The analysis was performed using the Chi-square or Fischer's exact tests, with the outcome being the specific admission nursing consultation for SARS-CoV-2. Results: Among the 1,272 individuals investigated, 21.3% (95% CI: 19.1-23.6) tested positive for antibodies against SARS-CoV-2. Of these, 10.3% (95% CI: 7.0-14.6) underwent a specific nursing consultation for SARS-CoV-2. The most prevalent signs and symptoms were loss of taste (33.2%) and smell (32.8%), body aches (28.8%), and fever (28.4%). The analysis indicated associations between contact with symptomatic COVID-19 case (p=0.039), contact in the yard with a prisoner with COVID-19 (p=0.012), and sore throat (p=0.010), with the outcome. Conclusions: The low prevalence of specific nursing consultations for SARS-CoV-2 and the high prevalence of COVID-19 reinforce the need for mandatory implementation of this strategy in groups living in closed environments. Furthermore, nursing consultations based on the nursing process must be adopted as a public health measure.